Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


The Brainliest Answer!
 x^{m} ( x^{n} + x^{n-2} )= x^{5} +x³
 x^{m} *x x^{n} (x²+i)/x²= x³(x²+1
 x^{m+n} =x³*x²= x^{5}
⇒ m+n=5
from this we can have m=0 and n=5
                             or  m=1 and n=4
                             or  m=2 and n=3
                             or  m=3 and n=2
                             or  m=4 and n=1  or m=5 and n=0
1 5 1
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts